Contextualising Jesus’ Teaching on Marriage and Adultery in Selected Church Denominations in Ibadan (2014)
Conflicts between Jesus’ teachings on marriage and adultery and some church traditions have resulted in misinterpretation of some bible passages and wrongly premised church doctrines. Previous research has highlighted Jesus' teachings as a stratagem against the high rate of marital problems among Christians, but has not adequately examined the conflict between Jesus' teachings and church traditions on marriage and adultery. This study, therefore, examined Jesus’ teachings on marriage and adultery in the Synoptic Gospels to determine the extent to which they aligned with selected church traditions and the effects of these on the churches. The study was premised on Abogunrin’s model of contextualisation. Eight Roman Catholic Churches (RCC), 15 Baptist Churches (BC) and 12 Celestial Church of Christ (CCC) in Ibadan North, North East, South East, North West and South West local government areas were purposively sampled. This was because they adequately represented the Mainline, Evangelical and the African Initiated Churches. Five hundred and fifty-four copies of a questionnaire were administered to purposively selected church leaders and members in the churches. In-depth interviews were conducted with 248 adults: married but separated (134), divorced and remarried (102), divorced based on restitution (12). Two focus group discussions were held with 25 people from each local government. Additional information was sought from church publications. Mark 10:1-12, Matthew 19:3-12 and Luke 16:18 were exegetically analysed. Quantitative data were subjected to percentages. Jesus' teachings on marriage and adultery centred on the Christian concept of virtues across the Synoptic gospels. In Matthew, Jesus prescribes monogamy (Matthew 19:4; Mark 10:8), conceiving of sex as a mono-partner affair, which precludes adultery and fornication (Matthew 5: 27-30). He teaches re-marriage as a venture in sinful re-union (Matthew 19:5; Luke 16:18). Within marriage, He recognises a strict adultery-tied divorce (Matthew 19:9) or no divorce (Mark 10: 9-12). All the churches situated sex within marriage and monogamy, but accommodated remarriage on differential grounds: RCC and BC officially disallowed remarriage on grounds of broken covenantal marriages, and divorce caused by desertion, adultery and unbeliever partnership. The RCC offered remarriage in cases of invalid marriages; and CCC on grounds of childlessness, adultery and desire for a male child; but BC only for widows. Consequently, there was a higher rate of divorce in CCC (CCC=60.0%, BC=35.0% and RCC= 5.0 %) than in RCC and BC. Polygyny, though doctrinally approved in CCC, and disapproved in RCC and BC, was a practice in RCC: 3.0% and BC: 24.0%. Paradoxically, while 85.0% of the respondents in the CCC recommended remarriage as an effective intervention in broken marriages, 55.0% of BC respondents and 30.5 % of RCC desired remarriage after divorce. The teachings in Roman Catholic and Baptist churches were largely consistent with Jesus' teaching on marriage and adultery; those of Celestial Church of Christ deviated completely from them. However, in practice, none of the churches aligned with Jesus' standards. Therefore, to keep within Bible-based prescriptions, the churches should align with the teachings of Jesus in theory and practice, but should be pragmatic in applying Jesus' principles